Cellular Stress Impact on Yeast Activity in Biotechnological Processes—A Short Overview - Madalina Postaru; Alexandra Tucaliuc; Dan Cascaval; Anca-Irina Galaction (Microorganisms, 2023)
The importance of Saccharomyces cerevisiae yeast cells is known worldwide, as they are the most used microorganisms in biotechnology for bioethanol and biofuel production. Also, they are analyzed and studied for their similar internal biochemical processes to human cells, for a better understanding of cell aging and response to cell stressors. The special ability of S. cerevisiae cells to develop in both aerobic and anaerobic conditions makes this microorganism a viable model to study the transformations and the way in which cellular metabolism is directed to face the stress conditions due to environmental changes. Thus, this review will emphasize the effects of oxidative, ethanol, and osmotic stress and also the physiological and genetic response of stress mitigation in yeast cells.